Perfil da REF dos anos 1999-2012 - Scavone, Lucila [UNESP] (FapUNIFESP (SciELO), 2013)
This paper originates from a larger research on gender and feminist academic outputs in Scientific Journals on this field, with a singular methodology. It studies the thematic priorities of the Revista Estudos Feministas from 1999 to 2012, through the survey of all papers published during this period. It analyses the consistency of its content with the proposed editorial policy, as well as the trends and characteristics of its publications. © 2013 by Revista Estudos Feministas.
Profile of the REF from 1999 to 2012
Keywords: Editorial policy; Editorial trends; Feminist studies journal; Published fields